A critical analysis of a thirty-five year judicial interplay in riba case - Tauheed Ullah, Siddiqui; Muhammad, Musa; Mohd Yusoff, Syarah Syahira (2024)
Pakistan has long been undergoing multiple litigations and judicial rounds of misadventures over thirty-five years in pursuit of elimination of riba from the national economy. The founder of Pakistan, Quaid-i-Azam Muhammad Ali Jinnah had aspired to see the research organization of the State Bank to evolve an indigenous economic model based on Islamic principles instead of relying upon the western system in his address in the inaugural ceremony of State Bank of Pakistan in 1948.1 Likewise, all the three constitutions also enunciated earliest elimination of riba as a part of principles of policy. This article investigates as to why after all the founder’s aspiration and the constitutional enunciations, riba could not be eliminated from the national economy so far. It will be doctrinal research that explores and analyses critically various aspects of the delays and deferments of the judicial proceedings and process in implementation of the judgements of the apex courts of Pakistan.